Dr Malondialdehyde as an independent predictor of body mass index in adolescent girls - Klisic, Aleksandra (Journal of Medical Biochemistry, 2022)
Objective: Given the fact that the studies that examined oxidative stress in relation to obesity that included late adolescents are scarce and show inconclusive results we aimed to investigate a wide spectrum of nitro-oxidative stress biomarkers [i.e., malondialdehyde (MDA), xanthine oxidase (XO), xanthine oxidoreductase (XOD), xanthine dehydrogenase (XDH), advanced oxidation protein products (AOPP) and nitric oxide products (NOx), as well as an antioxidative enzyme, i.e., catalase (CAT)] in relation with obesity in the cohort of adolescent girls ages between 16 and 19 years old.Patients and Methods: A total of 59 teenage girls were included in this cross-sectional study. Binary logistic regression analysis was performed to examine possible associations between biochemical and nitro-oxidative stress markers and body mass index (BMI). Results: There were not significant differences between oxidative stress markers between normal weight and overweight/obese girls (i.e., AOPP, XOD, XO, XDH) and CAT, except for MDA (p
Keywords: adolescents, inflammation, obesity, oxidative stress